The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/app.44115
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature CO sensing by polyaniline/Co3O4 nanocomposite

Abstract: Polyaniline/cobalt oxide (PANI/Co 3 O 4 ) nanocomposites have been investigated for their sensitivity towards carbon monoxide (CO) gas at room temperature. The Co 3 O 4 nanoparticles were prepared by ultrasound assisted coprecipitation method and then incorporated into the PANI matrix. Fourier transform infrared spectroscopy and ultraviolet-visible spectroscopy, powder X-ray diffraction, and field emission scanning electron microscopy have been used to characterize the nanomaterials. The PANI/Co 3 O 4 nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…We have previously reported the sensing performance of several PANI and polypyrrole systems [15,18,[29][30][31]. In this work, we report the development of PANI/ZnO nanocomposite sensor for RT methane detection.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the sensing performance of several PANI and polypyrrole systems [15,18,[29][30][31]. In this work, we report the development of PANI/ZnO nanocomposite sensor for RT methane detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent era, 1D nanostructures of intrinsically conducting polymers (ICPs) have attracted scientists owing to their higher surface area, high tendency to form anisotropic structure, metal‐like conductivity, highly conjugated molecular structure and promising application in nanodevices . Among the different ICP, 1D polyaniline (PANI) is highly preferred due to its ease of synthesis with variation of pH , reverse doping‐dedoping character and good environmental stability , making it suitable for applications in chemical sensors, biosensors, light emitting diodes, supercapacitors, electronic devices . 1D PANI can be prepared using different proton donor such as camphor sulfonic acid, oxalic acid, hydrochloric acid, and so on to produce variable physical and chemical characteristics of PANI .…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline (PANI) is an intrinsically conducting polymer (ICP) possessing the advantages of modifiable electrical conductivity, good environmental stability, inexpensive monomers, and ease of synthesis. Due to its good sensitivity towards CO gas at room temperature, it has been investigated for combination with metal oxide to form nanocomposites [18]. Although several studies have demonstrated that the sensing temperature of SnO 2 powder coatings can be lowered by many means such as doping with noble metals [19,20] or PANI [21,22,23], and deposition onto various nanostructured templates [24,25], for application in gas sensors, to the best of our knowledge, the sol-gel SnO 2 particle coating has not yet been drop-coated directly with various amounts of PANI for the optimization of low-temperature CO sensing performance.…”
Section: Introductionmentioning
confidence: 99%